Renal dysfunction in patients with chronic toxic hepatitis and ways of its correction - Kvasnytska, O.; Gozhenko, A. (Journal of Education, Health and Sport, 2023)
The aim of the study was to study the effectiveness of the long-acting angiotensin-converting enzyme (ACE) inhibitor Lisinopril in the correction of renal dysfunction in patients with chronic hepatitis (CH).It was found that in patients with СH under conditions of spontaneous diuresis, the glomerular filtration rate (GFR) decreases by 1.33 times against the background of a decrease in water reabsorption (p<0.05) and a tendency to a decrease in sodium excretion. During a 2-hour water load, a 3-fold decrease in GFR (p<0.05) was revealed with a slight decrease in water reabsorption and a decrease in sodium and potassium excretion in the urine (p<0.05). The occurrence of such disturbances in response to exercise indicates functional changes that may be due to intrarenal vasospasm as a result of activation of the interstitial renin-angiotensin system. The іnclusion of Lisinopril at a dose of 2.5 mg in the treatment regimen had a positive effect both on the clinical symptoms of hepatitis - a decrease in the activity of ALT, AST, urea (p<0.05), and on the functional state of the kidneys, mainly due to the effect on filtration processes. This is especially clearly demonstrated by the implementation of the water load: an increase in diuresis by 2 times (p<0.05) against the background of an increase in the glomerular filtration rate by 3 times (p<0.05), excretion of sodium and potassium (p<0.05). This indicates an increase in the adaptive function of the kidneys when included in the treatment ACE inhibitor.